Health Problems in Individuals With PWS Are Associated With Lower Quality of Life for Their Parents: A Snapshot in the Brazilian Population - Amaro, Alexandre Slowetzky; Rubin, Daniela Andrea; Teixeira, Maria Cristina Triguero Veloz; Ferreira, Arcenio José; Rodrigues, Graciele Massoli; Carreiro, Luiz Renato Rodrigues (Frontiers in Pediatrics, 2022)
Prader-Willi syndrome (PWS) is a complex genetic disorder requiring interdisciplinary team monitoring and intensive care by parents. So far there is little information on people with PWS in Brazil. Our aim was to describe health problems and treatments used by people with PWS in Brazil and their relationship to their parents' quality of life. Parents answered questionnaires about their child’s medical and exercise history, behavior problems, sociodemographic characteristics, and their own quality of life. Results: The responses of the participants showed similar health problems as in other countries. Anxiety and tantrums were the behavioral problems most commonly cited by parents. Parents of people with PWS had lower scores in respect of quality of life than the Brazilian population. Behavioral problems in individuals with PWS were negatively associated with their parents' quality of life. Behavioral and medical conditions in the children were associated with reduced quality of life in the parents. We conclude that heath care should not only be directed toward those with PWS, but also their parents.